Technology Disaster: Impact and Influence of Online Loans on Students' Social Environment - Rohmadi, Febri Dwi; Mauila, Ashfi Mazida (Proceeding International Conference on Religion, Science and Education, 2025)
Online loans or pinjol are money lending services made by financial service providers as a form of technological advancement. Services with a borrowing system with a Peer To Peer Lending system that brings together creditors and debtors online. Online loans have become a favorite place for all people to borrow money. The easy and fast application system makes this online loan a lot of access. The requirements only use ID cards and selfie photos, in contrast to conventional banks that use various requirements including collateral. The consequences of this pinjol facility are hefty interest rates and fines. The research focuses on students who are trapped in online loans. Students who are considered intellectuals who think critically have fallen into the pinjol circle. Students relatively often use online loans to fulfill tertiary needs which include fashion, beauty, online gambling, and other consumptive needs. A high debt burden can trigger stress because it is faced with the reality of not having readiness in money management. High interest rates and fines put pressure and affect the social environment of students. Social impacts can have an impact on the behavioral attitudes accepted by victims by the surrounding community. As a result, many students end their lives or commit suicide because they cannot bear such a heavy burden. There have been many Indonesian suicides caused by online loans. The interest given by the pinjol platform causes the nominal loan to be borrowed even higher. This technological disaster, if not resolved immediately, will cause more victims to be trapped in the negative impact of pinjol. The social aspects that arise emphasize the influence of the surrounding environment in making financial decisions. The use of online loans in society has become commonplace and natural, making other people not hesitate to access them.